Intercultural Training: Learn to avoid treading on other people’s toes or experience walking in the other person’s shoes - Rygg, Kristin (FLEKS - Scandinavian Journal of Intercultural Theory and Practice, 2014)
This article raises the question of whether the traditional approach in intercultural training focusing on knowledge about cultural differences and skills to avoid culture clash is sufficient in order to prepare intercultural communication trainees for dynamic and psychologically demanding multicultural environments. Inspired by the concept of mentalizing in the psycho-therapeutic method called Mentalization-based treatment, training that encourages imaginatively “seeing the other from the inside and oneself from the outside” is suggested as better able to prepare for complex intercultural realities. Tolerance is seen as tolerance for being in the intercultural process as much as tolerance for others’ differences. A theoretical discussion between the notion of mentalizing in mentalization-based treatment and perceptions of empathy, imagination and mindfulness further provides insight into the role of interactive tools such as case work and role plays in intercultural training. These, in turn, are seen as best suited to fulfil the goals and ambitions of the theories. However, experiences gained from them must be verbalized in order to cause increased awareness.